Effect of proactive personality on career adaptability of higher vocational college students: the mediating role of college experience - Fang, Min; Pan, Runsheng; Ding, Rongqi; Hou, Zhijin; Wang, Danni (Frontiers in Psychology, 2024)
For higher vocational students, the college stage is an important period in their career development, and the college experience plays an important role in the relationship between their proactive personality and career adaptability, which in turn has a significant impact on their future career development. From the perspective of social cognitive career theory and taking 476 vocational students as samples, this paper explores the mediating role of college experience between proactive personality and career adaptability of vocational college students. The college experience scale is revised for higher vocational students, and it is verified to have good reliability and validity. SPSS and Amos were used to conduct correlation analysis，and the PROCESS macro was used for mediating effect analysis. The results show that the college experience of vocational students plays a partial mediating role in the effect of proactive personality on career adaptability. This work innovatively uses social cognitive career theory to explore the role of college experience in the relationship between proactive personality and career adaptability among vocational students. The theoretical models are established and empirical verification is conducted, confirming that higher vocational students' college experience can affect their career adaptability. These results provide empirical evidence for vocational colleges to improve the career guidance of college students, and intervention measures are proposed to enhance students' career adaptability during school years, thus promoting their sustainable development.